Forever words : the unknown poems - Cash, Johnny (Blue Rider Press, an imprint of Penguin Random house LLC, 2016)
Present a collection of previously unpublished poems and lyrics by the legendary music icon that is complemented by original handwritten documents sharing insights into his observations about culture, family, fame, freedom, mortality and Christmas.